2018
DOI: 10.1038/s41598-018-23454-8
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of the Neuregulin 1/ErbB system after skeletal muscle denervation and reinnervation

Abstract: Neuregulin 1 (NRG1) is a growth factor produced by both peripheral nerves and skeletal muscle. In muscle, it regulates neuromuscular junction gene expression, acetylcholine receptor number, muscle homeostasis and satellite cell survival. NRG1 signalling is mediated by the tyrosine kinase receptors ErbB3 and ErbB4 and their co-receptors ErbB1 and ErbB2. The NRG1/ErbB system is well studied in nerve tissue after injury, but little is known about this system in skeletal muscle after denervation/reinnervation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…These factors are often assessed as markers of denervation in adult skeletal muscle (Rowan et al, 2012;Sekiguchi et al, 2012;Hendrickse et al, 2018;Sonjak et al, 2019). The reduction in expression of these transcripts following RT supports our laboratory's previous findings (Kelly et al, 2018a) and provides direction toward other possible targets for assessment in muscle denervation-reinnervation cycling, including ERBB3 (Erb-B2 receptor tyrosine kinase 3) (Morano et al, 2018) and MAGED1 (melanoma antigen gene family D1) (Magnusson et al, 2005). Like these denervation markers, expression of genes linked to neural apoptosis was increased with aging and reduced with exercise.…”
Section: Genes Linked To Dynamics Of Denervation and Neural Apoptosissupporting
confidence: 81%
“…These factors are often assessed as markers of denervation in adult skeletal muscle (Rowan et al, 2012;Sekiguchi et al, 2012;Hendrickse et al, 2018;Sonjak et al, 2019). The reduction in expression of these transcripts following RT supports our laboratory's previous findings (Kelly et al, 2018a) and provides direction toward other possible targets for assessment in muscle denervation-reinnervation cycling, including ERBB3 (Erb-B2 receptor tyrosine kinase 3) (Morano et al, 2018) and MAGED1 (melanoma antigen gene family D1) (Magnusson et al, 2005). Like these denervation markers, expression of genes linked to neural apoptosis was increased with aging and reduced with exercise.…”
Section: Genes Linked To Dynamics Of Denervation and Neural Apoptosissupporting
confidence: 81%
“…Further, ERBB4 mRNA was strongly downregulated in DMD muscle (−6.2-fold; adjusted P = 9.5 × 10 −6 ). ERBB4 is a cell-surface receptor neuregulin, and the NRG1/ERBB4 pathway has been extensively studied in hypoxia, TGF-β and fibrosis in the heart, kidney and neuronal cells where it plays a protective role and can be downregulated in disease states ( 38 , 39 ). In skeletal muscle, it appears important for mitochondrial function, and deficiency can lead to defects in oxidative phosphorylation ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…NRG-1 contains an epidermal growth factor-(EGF-) like domain that can bind to and activate receptor tyrosine kinases of the ErbB family (ErbB2, ErbB3, and ErbB4), exerting its role in cell survival, proliferation, migration, and differentiation [15,16]. All of the ErbB receptors are mainly present at the NMJ [17], and NRG-1 acts as a medium between terminal Schwann cells and motor axons, between motor axons and muscles, and between different muscle fibres [18,19]. Previous studies have shown that sepsis can induce a reduction in NRG-1 in the skeletal muscle system [20,21].…”
Section: Introductionmentioning
confidence: 99%